Latent Acquisition of Timed Responses in Cerebellar Cortex - Ohyama, Tatsuya; Mauk, Michael D (The Journal of neuroscience, 2001)
Evidence indicates that rabbit eyelid conditioning is mediated by plasticity in the interpositus cerebellar nucleus and in cerebellar cortex. Although the relative contributions of these sites are not fully characterized, evidence suggests that plasticity in the cerebellar cortex influences conditioned response amplitude and timing, whereas plasticity in the interpositus nucleus is necessary or permissive for conditioned response expression. Recent empirical and computational analyses suggest that, during training, plasticity is initially established in the cerebellar cortex, whereas conditioned response expression begins later as plasticity is induced in the interpositus nucleus. We used the dependence of response timing on the interstimulus interval (ISI) to test this latent learning hypothesis. Rabbits were initially trained using a tone conditioned stimulus (CS) with a relatively long ISI to a low-criterion threshold. The relative absence of plasticity in the interpositus nucleus was then examined via reversible disconnection of the cerebellar cortex. Later, to induce plasticity in the interpositus nucleus, subjects were trained to robust levels of conditioned response expression using a shorter ISI. Reversible disconnection of the cerebellar cortex at this time confirmed the presence of robust interpositus nucleus plasticity after the second phase. Subsequent probe trials with the long CS alone then revealed double-peaked responses whose peaks were appropriately timed to the two ISIs. The results are consistent with the hypothesis that temporally specific learning occurs first in the cerebellar cortex before the appearance of conditioned responses. This latent learning is expressed only after plasticity is induced in the interpositus nucleus.